Local Government and Welfare State: Study on Welfare Policy Practices of Kirtipur Municipality - Thakuri, Tika Bahadur; bista, Madan Kumar; Koirala, Shailendra Prasad (Shahid Kirti Multidisciplinary Journal, 2025)
The paper delves into the political framework of Nepal’s social welfare system of Local Level Government and its policy. The study explores the importance of social values, cultural roots and government’s decisions and their evolution in the political systems of Nepal. Similarly, it explores the significance of welfare system in local level government, their policy endeavour and ongoing impact on the subjects. The local level government structure and agencies are the important carriers of the change and welfare. The study is based on constructive interpretative nature of qualitative method, the non-probability purposive sampling with interview questions is used to explore the data of the study. The collective endeavour of Nepali cultural identity and structure has played a vital role in its polity in ancient, medieval, and early modern periods of its history. The local government system plays a greater role in bringing equal opportunity, recognition, participation and inclusion. The study explores the local government of Federal Democratic Republic of Nepal engages in basic needs-interest-based polity welfare system and need to wholistic governing welfare mechanism amongst the three tiers of government. Additionally, this paper touches upon the challenges and opportunities involved in constructing Nepal as a welfare state.